2018
DOI: 10.1021/acs.cgd.8b01099
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Single-Crystalline Na4Si24

Abstract: Na4Si24 is the precursor to Si24, a recently discovered allotrope of silicon. With a quasidirect band gap near 1.3 eV, Si24 has potential to transform silicon-based optoelectronics including solar energy conversion. However, the lack of large, pure crystals has prevented the characterization of intrinsic properties and has delayed deposition-based metastable growth efforts. Here, we report an optimized synthesis methodology for single-crystalline Na4Si24 with crystals approaching the millimeter-size scale with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…5 Si 136 [ 94 ] were discovered by exploring high-pressure chemistry of Na-Si system and are the promising precursors for synthesis of open framework Si 24 and Si 136 allotropes with quasi-direct bandgap. However, contrary to many other high-pressure syntheses, the Na 4 Si 24 compound cannot be easily obtained; the in situ studies indicated that it is due to complicated nucleation mechanism [ 23 ].…”
Section: In Situ Large-volume High-pressure Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Si 136 [ 94 ] were discovered by exploring high-pressure chemistry of Na-Si system and are the promising precursors for synthesis of open framework Si 24 and Si 136 allotropes with quasi-direct bandgap. However, contrary to many other high-pressure syntheses, the Na 4 Si 24 compound cannot be easily obtained; the in situ studies indicated that it is due to complicated nucleation mechanism [ 23 ].…”
Section: In Situ Large-volume High-pressure Synthesesmentioning
confidence: 99%
“…One consists of exploring very high pressures beyond the industrial limits (P > 20 GPa) in order to reach significantly unusual solids (for example room temperature superconductor [ 21 ], or polymerization of CaC 2 [ 22 ]) that would allow understanding the links between advanced properties and crystal structure/composition, which we will not consider in this paper. Another methodological approach, more pragmatic but still promising, consists of the in situ exploration of “traditional” industrial pressure scale for the design of new stable or metastable compounds by also playing with kinetics (e.g., for nanostructuring) and nucleation-growth mechanism for phase selection [ 23 ]. Fixing this “industrial limit” to 20 GPa, what we are actually doing in this review, is quite challenging, but it remains industrially accessible, for example, in advanced technology of production of sintered nanodiamond with advanced mechanical and optical properties [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…440 [22] removing metal atoms. [33][34][35][36][37] Here, based on recently synthesized 2Sr@B 6 C 6 (as a comparison, which is given in Supporting Information, we also show its unit cell in Figure 1a), [23] we study the structure of the porous 3D-B 6 C 6 by removing Sr atoms, the initial structure consists of 24 vertices with alternating C and B atoms, forming a truncated octahedral cage with six four-sided faces and eight six-sided faces. As shown in Figure 1b,c, the optimized structure contains some broken B-C bonds and the symmetry is reduced to C 1 2h (space group: P2/m) with lattice constants of a = 5.184 Å, b = 4.180 Å, c = 4.366 Å, angles of 𝛼 = 89.86°, 𝛽 = 𝛾 = 90°, volume of 94.615 Å 3 , and density of 2.403 g cm −3 , where the unit cell of this structure contains 6 B and 6 C atoms with a ratio of 1:1.…”
Section: Geometrymentioning
confidence: 99%
“…Since Takahashi & Bassett's original work in the late 1960s using laser heating to synthesize diamond from graphite, 2 laser heating at extreme conditions has enabled scientists to study matter at conditions relevant to planetary interiors 3,4 and also to synthesize a wide variety of new materials with unique phases and compositions. [5][6][7] Controlling the temperature within DACs has also led to recent reports of metal-hydride materials with superconducting phase transitions near room temperature. [8][9][10] In contrast to laser heating, solid-state laser refrigeration at extreme conditions has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%